Genomic characterization of antimicrobial-resistance and virulence factors in Salmonella isolates obtained from pig farms in Antioquia, Colombia. - María Isabel García-Álvarez; Juana L Vidal; Pilar Donado-Godoy; Jared Smith; Nikki Shariat; María Fernanda Valencia; Luis M Gómez-Osorio; Sara López-Osorio; Jenny J Chaparro-Gutiérrez (PLoS Neglected Tropical Diseases)
Background Occurrence of antimicrobial-resistant Salmonella strains has been reported worldwide, because of inappropriate use of antimicrobial products in either humans or animals. The presence of multidrug resistant Salmonella in pig production systems had been reported in Antioquia, Colombia. Aim To identify antimicrobial resistance genes (ARG) in different Salmonella spp. strains isolated from pig productions in Antioquia, Colombia. Methods: Samples were received at the Diagnostic Unit of the Faculty of Agrarian Sciences at the University of Antioquia, from January 1, 2019, to January 2021. A total of 28 isolates of Salmonella spp. were included, which presented phenotypic resistance to more than one antibiotic used in pig farms. Whole genome sequencing (WGS) was performed in the Unit of Genomic of Agrosavia using an automated pipeline from the GHRU- Sanger Institute, employing the Illumina MiSeq platform. Results WGS revealed 34 ARGs among these isolates. In 25 isolates (89%) more than two ARGs were found. Genes encoding resistance were found for 10 different groups of antibiotics (beta-lactam, aminoglycosides, chloramphenicol, rifampicins, lincosamides, fluoroquinolones, tetracyclines, sulfonamides and trimethoprim). The most frequently observed MDR profile in Typhimurium isolates was AMP-CEX-CEP-CEF-EFT-CEQ-FLU-ENR-TE-FFC-SXT. Conclusion The presence of multi-drug resistant Salmonella strains in pigs destined for human consumption in Antioquia, Colombia was determined. This research emphasizes the utmost importance of epidemiological tools to understand the presence and spreading of antimicrobial resistance genes in pig farms. Additionally, it highlights the critical need for developing educational programs and public policies to help reduce the spread of antimicrobial resistance in production systems.